2007
DOI: 10.1016/j.brainres.2006.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Podokinetic after-rotation in Parkinson disease

Abstract: Walking on a rotating platform for 15 minutes causes healthy subjects to involuntarily turn when walking without vision. This adaptive response, called podokinetic after-rotation (PKAR), uses the same kinematic patterns as voluntary turning suggesting that PKAR and voluntary turning share common mechanisms. The purpose of this study is to determine whether people with Parkinson disease (PD), a condition that produces substantial disability from turning difficulties, can adapt to the rotating platform. Initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…No abnormality in adaptation to proprioceptive stimulation is obvious, in keeping with other studies based on more complex situations. 18,37 On the one hand, one wonders about the subsistence of any major deficit in proprioceptive coding or integration in PD with respect to other movement disorders, at least as far as postural tasks are concerned. 38 On the other, one would argue that a relatively powerful proprioceptive inflow, as that induced by the present vibration protocol, could have easily overcome any subtle impairment in kinesthesia.…”
Section: Are Body Oscillations Coupledmentioning
confidence: 99%
“…No abnormality in adaptation to proprioceptive stimulation is obvious, in keeping with other studies based on more complex situations. 18,37 On the one hand, one wonders about the subsistence of any major deficit in proprioceptive coding or integration in PD with respect to other movement disorders, at least as far as postural tasks are concerned. 38 On the other, one would argue that a relatively powerful proprioceptive inflow, as that induced by the present vibration protocol, could have easily overcome any subtle impairment in kinesthesia.…”
Section: Are Body Oscillations Coupledmentioning
confidence: 99%
“…We have demonstrated that kinematic patterns employed during PKAR following exposure to the rotating treadmill are similar to those used in voluntary turning [4]. Furthermore, we have shown that people with mild PD are able to adapt to walking on the rotating treadmill and demonstrate robust PKAR [6]. This latter finding is crucial because successful rehabilitation is dependent on the individual's ability to adapt and modify behavior with treatment.…”
Section: Introductionmentioning
confidence: 67%
“…Subjects walked for as long as they were able, up to 5 minutes, and were given rests as needed until they had accumulated 10 or 15 min, respectively, of total treadmill time. For more detailed information on experimental setup, refer to Hong et al [6].…”
Section: Data Collectionmentioning
confidence: 99%
“…The subjects stepped or kneel-stepped on the treadmill for three 5-min intervals, with 5-min breaks between sets (Figure 1). Previous studies have demonstrated that three 5-min intervals with 5-min breaks between produce very similar responses as 15 continuous min of PK stimulation (Hong et al 2007). As such, we used the three 5-min intervals to make the kneeling protocol tolerable.…”
Section: Protocolmentioning
confidence: 92%
“…After PK stimulation, the subjects stepped in place in standing on a stationary surface for 10 min while we measured their PKAR. The duration of 10 min was chosen instead of 30 min based on previous work demonstrating that results obtained from 10 min of PKAR were not significantly different from those obtained using 30 min of PKAR (Hong et al 2007). A blindfold and earplugs were provided to subjects to eliminate visual and auditory inputs during PKAR.…”
Section: Protocolmentioning
confidence: 99%